Preparation and adsorption properties of TiO2/MoS2 nanocomposites. (22nd February 2019) - Shao, Lixiang; Liu, Jinghui; Li, Fan; Yang, Jinghe; Zhang, Xiaoya; Li, Songjie; Li, Yuanyuan; Sun, Panfei
Abstract: A TiO2 /MoS2 nanocomposite was synthesized by the hydrolysis sol-gel of TiO2 combined with situ hydrothermal preparation of MoS2 . The properties of prepared TiO2 /MoS2 nanocomposites were studied by the adsorption of methylene blue solution. The TiO2 /MoS2 nanocomposite was prepared at 200 °C with different ratio of Mo/Ti. For the nanocomposite with ratio of Mo/Ti 1:7, it was proved to be anatase phase of TiO2 with a particle size of 10 nm. There are some small holes on the surface of TiO2 caused by the shedding of MoS2 with particle size of 2 nm. The synthesized TiO2- MoS2 nanocomposite has a good adsorption capacity for methylene blue and the maximum adsorption capacity for methylene blue dye is up to 32.299 mg g −1 . The adsorption of methylene blue on the surface of TiO2 /MoS2 composites is single molecule adsorption.